2019
DOI: 10.1021/acs.jpcc.9b03782
|View full text |Cite
|
Sign up to set email alerts
|

Singular Nonmagnetic Semiconductor ScH3 Molecular Nanowire: A New Type of Room-Temperature Spintronic Material

Abstract: Trihydride molecular nanowire (ScH 3 ) is a nonmagnetic semiconductor with a direct band gap and could retain its structure at temperatures up to 1200 K. In this paper, we report that ScH 3 could be a new type of ideal room-temperature spintronic material. The simulations of the ScH 3 field-effect transistor show that ScH 3 turns into a ferromagnetic (FM) half-metal upon electron-or hole-doping induced by the applied gate voltage. State-of-the-art ab initio calculations reveal that the FM of electrondoped ScH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…As shown in Fig. 4(a-f and S25 in Supporting Information, the test calculations with the SCAN 26,27 and HSE06 hybrid functionals [27][28][29][30] confirmed that S-1, S-2, S-3,S-4, S-5 and S-6 crystals are semiconductors, whereas S-7 and S-8 are metals.…”
Section: Electronic Band Structurementioning
confidence: 68%
See 1 more Smart Citation
“…As shown in Fig. 4(a-f and S25 in Supporting Information, the test calculations with the SCAN 26,27 and HSE06 hybrid functionals [27][28][29][30] confirmed that S-1, S-2, S-3,S-4, S-5 and S-6 crystals are semiconductors, whereas S-7 and S-8 are metals.…”
Section: Electronic Band Structurementioning
confidence: 68%
“…In the electronic band structures and elastic constants calculations, Monkhorst Pack k-point meshes with the grid density of 0.03×2π Å −1 were applied to achieve a total energy convergence of ≤ 1 meV per atom. For electronic band structures, the test calculations with the strongly constrained and appropriately normed (SCAN) nonempirical density functional 26,27 and HSE06 hybrid functional [27][28][29][30] also had been performed. In the GW and GW-BSE calculations, the plane wave cutoff energy, number of bands, Monkhorst-Pack grid, dielectric matrix cutoff and number of conduction bands have been converged carefully to 700 eV, 10 × 10 × 10, 450 eV and 256, respectively.…”
Section: Electronic Band Structures Elastic Constants and Optical Spmentioning
confidence: 99%
“…13 the mechanical stability, dynamical stability, and structural stability of the S-1, S-2, S-3, S-4, S-5, and S-6 GaNGeC quaternary compound semiconductors have been demonstrated by using the calculated elastic constants, phonon dispersion, binding energy, and formation energy of the systems. Here, quantum molecular dynamics (QMD) simulations [29][30][31] have been performed to check the thermal stability of the systems. As shown in Fig.…”
Section: Pccp Papermentioning
confidence: 99%
“…Thus, HM can provide 100% spin polarized current. Up to now, HMs have been found in Heusler alloys, [4][5][6][7] diluted magnetic semiconductors, 8,9 perovskite compounds, 10,11 two dimensional materials, [12][13][14] zinc blende compounds, 15,16 nanowires, 17 nanoribbons 18,19 and nanotubes, 20 etc. SGS was rstly theoretically proposed and experimentally veried in Codoped PbPdO 2 , 21 where one spin channel is semiconducting and the other has an almost vanishing zero-width band gap at Fermi level.…”
Section: Introductionmentioning
confidence: 99%